2021
DOI: 10.1016/s0140-6736(21)01694-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of heterologous versus homologous prime-boost schedules with an adenoviral vectored and mRNA COVID-19 vaccine (Com-COV): a single-blind, randomised, non-inferiority trial

Abstract: Background Use of heterologous prime-boost COVID-19 vaccine schedules could facilitate mass COVID-19 immunisation. However, we have previously reported that heterologous schedules incorporating an adenoviral vectored vaccine (ChAdOx1 nCoV-19, AstraZeneca; hereafter referred to as ChAd) and an mRNA vaccine (BNT162b2, Pfizer–BioNTech; hereafter referred to as BNT) at a 4-week interval are more reactogenic than homologous schedules. Here, we report the safety and immunogenicity of heterologous schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

68
407
4
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(486 citation statements)
references
References 20 publications
68
407
4
7
Order By: Relevance
“…In our study, this effect might be altered due to the difference in time of application of the booster vaccination and due to different vaccines used for prime vaccination. Earlier data had already shown similar results to those presented here when comparing an AZD1222/BNT162b2 combination with a homologous BNT162b2 prime-boost vaccination [33].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, this effect might be altered due to the difference in time of application of the booster vaccination and due to different vaccines used for prime vaccination. Earlier data had already shown similar results to those presented here when comparing an AZD1222/BNT162b2 combination with a homologous BNT162b2 prime-boost vaccination [33].…”
Section: Discussionsupporting
confidence: 88%
“…The results of a single-blind randomised British study, in which the four possible vaccine combinations of AZD1222 and BNT162b2 were compared with one another, are very interesting and promising. These researchers report about 9-fold higher mean anti-S IgG titres in sera from heterologous AZD1222/BNT162b2 vaccinees compared to individuals immunised twice with AZD1222 [19] which is largely in accordance to our results. In a study from Sweden, markedly higher anti-S and anti-RBD IgG titres were observed after heterologous vaccination (AZD1222/mRNA-1273) compared to the homologues AZD1222 scheme.…”
Section: Discussionsupporting
confidence: 92%
“…The results presented by us on the antibody response after heterologous SARS-CoV-2 vaccination are consistent with the few available clinical studies [17, 19, 21, 16, 18, 20]. In June 2021, a randomised study from Spain has already demonstrated that the heterologous vaccination scheme is suitable for generating a robust immune response.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, recruitment for phase I/II clinical trials with the AstraZeneca and Pfizer mRNA SARS-CoV-2 vaccine combination is currently ongoing. Clinical trials with individuals that received the first dose from AstraZeneca and the second dose of Pfizer mRNA vaccine revealed potentiation of the immune responses, as measured by increased S protein binding antibodies and enhanced neutralizing antibody levels [17,18]. Thus, heterologous combinations of vaccines might provide an advantage for vaccination.…”
Section: Discussionmentioning
confidence: 99%